Integritas dan Kepercayaan Bidan untuk Menciptakan Kemitraan dengan Dukun di Kota Mamuju - Nurgahayu Nurgahayu; Halida Thamrin (FORIKES, 2023)
The position of midwives and traditional healers in partnership places midwives as birth attendants and changes the function of the traditional healers. In this case, the function of the traditional healers, which was originally used as the main helper in childbirth, has become a midwife partner whose function is to care for mothers and babies on a non-medical basis. The purpose of this study was to analyze the relationship between integrity and the trustworthiness of midwives in partnering with traditional healers in Mamuju City, West Sulawesi Province. This study used a cross-sectional approach. The population of this study was 99 village midwives, while the sample was 53 village midwives who were selected by accidental sampling technique. Integrity and trust were measured by filling out a questionnaire. Data analysis was carried out descriptively, followed by hypothesis testing using Fisher's exact test. The results of the analysis showed that integrity and trust research was at the